Validity of New Ballard Score Untill 7th Day of Postnatal Life In Preterm Neonate (Bangladesh Journal of Child Health, 2017)
Background: Premature infant mortality & morbidity is influenced by intrauterine growth & maturation. In our perspective unavailability of accurate LMP from mother, early USG report or home delivered preterm baby that admitted after 4th day of postnatal age create great dilemma regarding the assessment of gestational age (GA).Objective: To validate the New Ballard Score (NBS) until 7th day of postnatal age in preterm neonate.Methods: This observational cross sectional study was conducted in pediatric ward, Rajshahi Medical College Hospital from 1st January 2009 to 31st December 2009. A total of 129 preterm neonate, GA ranging from 29wk to 35 wk, without any medical problem were included in this study. Accurate documentation of LMP of mother and USG during early pregnancy period were available for each study sample. GA of the babies were determined by NBS on 1st, 5th and 7th postnatal age and compaired with LMP & USG based GA. Various raw score was obtained from broken total score in D1 compared with D5 & D7. LMP based GA also compared with USG based GA.Results: Total NBS of D1 were tested with D5 & D7 for level of agreement & degree of correlation. For D1 with D5, r value was 0.97 and for D1 with D7, r value was 0.681. So, NBS of D1 positively correlated with NBS of D5 and D7. The total physical score also positively correlated with D1 versus D5 & D7 (r value 0.975 & 0.796). The total neurological score positively correlated with D1 versus D5 & D7 (r value 0.893 & 0.630). Neurological score were more significant than physical score. All p values were statistically significant (p value ?0.001). GA by NBS & LMP was positively correlated (r=0.94) as well as GA by NBS & USG (r=0.94). GA by NBS did not differ more than 2 weeks from LMP or USG based GA of any particular subjects.Conclusions: The tendency of over estimates the GA by NBS increased from Day 1 to Day 5 to Day 7. But the GA calculated from LMP & USG did not differ more than 2 weeks from GA by NBS. Thus NBS can be used as a clinical tool to detect GA up to Day 7 of postnatal life.Bangladesh J Child Health 2017; VOL 41 (1) :24-27